Discontinuous hydration improves germination and drought tolerance in Annona squamosa seedlings (Research, Society and Development, 2021)
The aim of this work was to determine if the discontinuous hydration of A. squamosa seeds benefit its seed germination and if the seedlings from these seeds have a greater tolerance to water deficit through the analysis of growth parameters. The experimental design was a completely randomized, in a 4x3 factorial, with four HD cycles in seeds (zero, one, two and three) and three water treatments (control with daily watering, and cycles of five and ten-intervals days between watering). Plant height, stem diameter, number of leaves, dry biomass, root/shoot ratio, leaf area, specific leaf area, and leaf area ratio were evaluated. Discontinuous hydration treatments benefited germination and promoted a better growth of the seedlings under water deficit cycles. The application of three HD cycles increased plant height, stem diameter, number of leaves, leaf area and dry matter of the seedlings compared to the other cycles. On the other hand, water suppression caused a reduction in the growth of A. squamosa, especially at ten-day intervals between watering. HD cycles in the seeds improved drought tolerance in the seedlings, mainly when three HD cycles are applied to the seeds, suggesting this is a good technique to produce seedlings better tolerant to environments with reduced water availability.